Point-of-care influences orchiectomy rates in pediatric patients with testicular torsion. Issue 4 (August 2019) - Romao, Rodrigo L.P.; Anderson, Katherine H.; MacLellan, Dawn; Anderson, Peter
Summary: Objectives: The objective of this study was to determine whether point-of-care (community hospitals vs. tertiary centers) or treatment-delaying variables (transfer, emergency room [ER] throughput, and distance traveled) affect orchiectomy rates in minors with testicular torsion (TT) using a national database. Study design: This was a retrospective cohort study using prospectively collected data by the Canadian Institute of Health Information (CIHI) between 2010 and 2015. All Canadian male patients in the CIHI database aged <18 years with TT based on International Classification of Diseases (ICD) codes were included, except for those residing in Quebec. Variables collected were age, type of treating institution (community small/medium, community large, or tertiary/academic), transfer for definitive treatment, road distance traveled, and ER throughput. The outcome was testicular loss based on intervention codes for orchiectomy/orchidopexy. Univariable and multivariable analyses were performed using logistic regression. Results: A total of 1713 minors with TT were included. Overall orchiectomy rate was 28%. Most patients (52%) were treated at tertiary hospitals. Small/medium community hospitals depicted the lowest odds of orchiectomy on univariable and multivariable analyses (odds ratio [OR] = 0.54, confidence interval [CI]: 0.37–0.79, p < 0.001); academic hospitals were also associated with a lower odds of orchiectomy than large community ones. Transfer and distance traveled were not associated with the outcome. Age >12 and ER throughput less than 1 h were significantly associated with lower orchiectomy rates. In a subgroup analysis of patients aged <12 years (n = 278), transfer was the only factor associated with increased risk of orchiectomy (OR = 2.41, CI: 1.09–5.33; p = 0.03). Discussion: This study showed that small and medium community hospitals had the lowest orchiectomy rates in minors with TT in Canada (Figure). However, on multivariable analysis, they performed similarly to tertiary/academic hospitals, with both being superior to large community hospitals. Transfer and distance traveled did not affect orchiectomy rates. Emergency room throughput had a statistically significant association with orchiectomy rates in every analysis and based on the study data would constitute the best target for policies aimed at reducing orchiectomy rates for TT in minors. The main limitation of this study is the inability to evaluate long-term testicular viability of patients not undergoing orchiectomy (i.e., true testicular salvage). Conclusions: Type of hospital treating facility (point-of-care) affects orchiectomy rates in minors with TT. Small/medium community hospitals depict the lowest orchiectomy rates in Canada. Transfer to another facility for definitive care and distance traveled did not affect orchiectomy rates, except in a subgroup analysis of prepubertal boys. Longer ER throughput and prepubertal age were consistently associated with loss of the testicle. Summary Fig. Testicular torsion treatment and outcomes by the type of treating facility. Figure